Contamination of the Clinical Microbiology Laboratory with Vancomycin-Resistant Enterococci and Multidrug- Resistant Enterobacteriaceae: Implications for Hospital and Laboratory Workers - Collins, Susan M. (American Society for Microbiology, 2001)
We surveyed environmental surfaces in our clinical microbiology laboratory to determine the prevalence of vancomycin-resistant enterococci (VRE) and multidrug-resistant Enterobacteriaceae (MDRE) during a routine working day. From a total of 193 surfaces, VRE were present on 20 (10%) and MDRE were present on 4 (2%) of the surfaces tested. In a subsequent survey after routine cleaning, all of the 24 prior positive surfaces were found to be negative. Thus, those in the laboratory should recognize that many surfaces may be contaminated by resistant organisms during routine processing of patient specimens.